2012
DOI: 10.1007/s00214-012-1141-y
|View full text |Cite
|
Sign up to set email alerts
|

The nature of the C–As bonds in arsaalkynes: an atoms in molecules and electron localization function study

Abstract: The nature of the C-As bonds present in a series of six neutral and anionic arsaalkynes was investigated. The optimized geometries, vibrational frequencies, and wavefunctions of all the studied species were computed using density functional theory (B3LYP/6-311??G(2d,2p)). To understand the bonding characteristics, Atoms in Molecules theory and topological analysis of the electron localization function were used. For comparison, natural bond orbital analysis was also performed. The results suggest that in five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 56 publications
(96 reference statements)
0
3
0
Order By: Relevance
“…[42]. A detailed study of method assessments for low‐energy conformers has been demonstrated by Bun Chan [47] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[42]. A detailed study of method assessments for low‐energy conformers has been demonstrated by Bun Chan [47] …”
Section: Resultsmentioning
confidence: 99%
“…A detailed study of method assessments for low-energy conformers has been demonstrated by Bun Chan. [47] The energetic analysis of this work mainly concerns on the low-(ttg) and high-energy conformers (ctg and ctt). The span of the conformers' energy was at least 4.8 kcal/mol.…”
Section: The Previous Conformational Studiesmentioning
confidence: 99%
“…Similarly, it is known that the ''nearsightedness'' of the off-diagonal terms in the first-order density matrix increases as the band gap increases. [14][15][16][17] The problem with these forms is that they require non-local information and this means that the connexion with real space (molecular structure, bonds and dihedral angles) is lost. Several local indicators have been recently proposed in the literature.…”
Section: Introductionmentioning
confidence: 99%